Energy characteristics of medium pressure steam boilers - Bezhan V. A.; Zhytarenko V. M.; Dalakov P. (Журнал інженерних наук)
The object of this study is the thermal and energy characteristics of medium pressure boilers of СНPP-1, four boilers CKTI-75/39F-2-4 and two boilers TP-150-2. All boilers operate on a common steam collector of 32 atm, at 420 °С. Fuel is a mixture of blast furnace gas and natural gas in the ratio of 0.7-0.9 volume particles. The characteristics of the blast furnace gas are not constant: the elemental composition, humidity, and dustiness of blast furnace gas change significantly. Analysis of operation of CHPP-1 medium pressure boilers of OJSC “Mariupol Metallurgical Combinat named after P. G. Ilyich” was carried out on the basis of the technical documentation and materials obtained during the ecological and thermal-technical tests of the boilers CKTI-75/39F-2-4 No. 7–9, and TP-150 No. 11, 12 of SU “Promavtomatika”. The main purpose of the analysis is to identify patterns that affect the operational characteristics of boilers, especially the efficiency. The analysis revealed the nature of the overall dependence of the efficiency on the load, as well as the dependence of the efficiency of the boilers on the load at different thermal parts of the blast furnace gas. After carrying out the balance tests, the dependencies of the exhaust gas temperature on the boiler load at different thermal parts of the blast furnace gas were established.